2022
DOI: 10.1038/s41524-022-00757-z
|View full text |Cite
|
Sign up to set email alerts
|

Perovskite synthesizability using graph neural networks

Abstract: Perovskite is an important material type in geophysics and for technologically important applications. However, the number of synthetic perovskites remains relatively small. To accelerate the high-throughput discovery of perovskites, we propose a graph neural network model to assess their synthesizability. Our trained model shows a promising 0.957 out-of-sample true positive rate, significantly improving over empirical rule-based methods. Further validation is established by demonstrating that a significant po… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
37
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 40 publications
(37 citation statements)
references
References 67 publications
0
37
0
Order By: Relevance
“…To overcome this difficulty, a recent study suggested that an ML model based on transfer learning is able to predict the synthesizability of perovskites with desirable band gaps. [ 52 ]…”
Section: Materials Design and Optimization Of Metal Halide Perovskitesmentioning
confidence: 99%
See 2 more Smart Citations
“…To overcome this difficulty, a recent study suggested that an ML model based on transfer learning is able to predict the synthesizability of perovskites with desirable band gaps. [ 52 ]…”
Section: Materials Design and Optimization Of Metal Halide Perovskitesmentioning
confidence: 99%
“…Charge-, spin-dependent ML potentials, [45][46][47][48] Ferroic phases Long-range charge/dipole interactions Charge-dependent ML potential [45,46] Excited states dynamics Hot carrier cooling Accurate description of non-adiabatic process, Nanoscale NAMD Excited states ML potential [49] PL mechanism of 0D MHPs Nanodomains Spin-dependent excited states ML potential [48,49] Materials design Holistic ML prediction High dimensional chemical space, Multiple property predictions Geometric learning, [50] Multi-task [51] /Transfer learning [52] High quality dataset for MHPs Data mining of experimental results, Dataset at high levels of theory Natural Language Processing, [53,54] Distributed data mining [55] Trial-and-error synthesis Controllable synthesis in various conditions, Automatic optimization of solution-based synthesis ML optimization for robotics synthesis [56][57][58] Adv. Energy Mater.…”
Section: Kinetic Process Crystallization and Formation Mechanism Solv...mentioning
confidence: 99%
See 1 more Smart Citation
“…There has been successes in using information from failed experiments, 89 but probabilistic models are more generally built from positive and unlabelled data for specific classes of material. 90,91 For more universal models, a large amount of diverse data is required. There has been progress in text mining of synthesis information from the literature.…”
Section: Machine Learning and Data-driven Approachesmentioning
confidence: 99%
“…In this case, positive-unlabeled (PU) classification is a reasonable problem setting affording a discriminant boundary between positive and unlabeled data 24 . We can determine the possibility of solid-solid phase transition in unlabeled data in a manner similar to using the PU setting to predict the synthesizability of materials 25,26 . We used four different models to decide on the discriminant boundary: random forest (RF), neural network (NN), support vector machine (SVM), and gradient boosting decision tree (GBDT) (Table S1).…”
mentioning
confidence: 99%